Medical service pricing and pharmaceutical supply chain coordination contracts under the zero-markup drug policy - Zhou, Nan; Li, Shiyang; Zhao, Gang; Li, Chengjiang; Yu, Na (Frontiers in Public Health, 2023)
Aimed at implementing the state policies of drug zero-markup policy and medical service fees adjustment for public hospitals, this study constructed game models of pharmaceutical supply chain which consisting of a drug supplier and a public hospital. The study obtained the optimal medical service level and pricing under the new state drug policies. In addition, it analyzed the impacts of the degree of public benefit of hospital on the medical service level, the medical service price, and the drug price. Finally, from the perspective of cooperation between drug suppliers and public hospitals, the specialized coordination contract was designed to maximize the overall social welfares. This study found an anomalous but meaningful conclusion, in the background of drug zero markup policy, a higher public benefit of hospital could increase the drug prices, but it could reduce the medical service prices more to cut down the overall treatment fees for the patients. The novel coordination contract can optimize the pharmaceutical supply chain and achieve a win-win situation for the drug suppliers, public hospitals and patients. When the public benefit of hospital is higher, the profit of decentralized decision-making supply chain is greater than the centralized one while the pharmaceutical supply chain will not coordinate itself. Keywords：Pharmaceutical supply chain, Medical service pricing, public benefit of hospital, Coordination contracts.